Clinical characteristics of smoking-related chronic pancreatitis - Hao, Lu; Liu, Yu; Dong, Zhi-Qi; Yi, Jin-Hui; Wang, Dan; Xin, Lei; Guo, Hong-Lei; He, Lin; Bi, Ya-Wei; Ji, Jun-Tao; Wang, Teng; Du, Ting-Ting; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Objective The pathogenesis of chronic pancreatitis (CP) is not completely clear. With further studies, smoking is toxic to the pancreas. This study classified smoking-related CP as a new etiology of CP and defined the cutoff of smoking. Design Patients with CP admitted from January 2000 to December 2013 were included in the study. The characteristics were compared between smoking patients, drinking patients, and a group of patients who never smoke or drink (control group). The cumulative rates of steatorrhea, diabetes mellitus (DM), pancreatic pseudocyst (PPC), pancreatic stone, and biliary stricture after the onset of CP were calculated, respectively. Results A total of 1,324 patients were included. Among them, 55 were smoking patients, 80 were drinking patients, and 1,189 were controls. The characteristics of smokers are different from the other two groups, especially in age at the onset and diagnosis of CP, initial manifestation, and type of pain. The development of DM (P = 0.011) and PPC (P = 0.033) was significantly more common and earlier in the smokers than in the other two groups. Steatorrhea also developed significantly more in the smokers than in the controls (P = 0.029). Smokers tend to delay the formation of pancreatic stones and steatorrhea. Conclusion The clinical characteristics of smoking-related CP is different from CP of other etiologies. A new type of CP, smoking-related CP, was put forward. Smoking-related CP should be separated from idiopathic CP and defined as a new independent subtype of CP different from alcoholic CP or idiopathic CP.